Reading Bond Films through the Lens of "Religion". Discourse of "the West and the Rest" Reading Bond Films through the Lens of "Religion" - Teemu Taira (Journal for Religion, Film and Media, 2019)
Religion has been absent from the study of James Bond films. Similarly, James Bond has been absent from studies on religion and popular culture. This article aims to fill the gap by examining 25 Bond films through the lens of "religion". The analysis suggests that there are a number of references to "religion" in Bond films, although religion is typically not the main topic of the films. Furthermore, there is a detectable pattern in the films: religion belongs primarily to what is regarded as not belonging to "the West" and "the West" is considered modern, developed and rational as opposed to the backward, exotic and religious "Rest". When religion appears in "the West", it is seen positively if it is related to Christianity and confined to the private sphere and to the rites of passage. In this sense, representations of religion in Bond films contribute to what Stuart Hall named the discourse of "the West and the Rest", thus playing a role in the maintenance of the idea of "the West". This will be demonstrated by focusing on four thematic examples from the films. This article also provides grounds for suggesting that reading Bond films through the lens of "religion" contributes to both Bond studies and studies on religion and popular culture.